Tocqueville, jansenism, and the necessity of the political in a democratic age: building a republic for the moderns - Selby, David A. ca. 20./21.Jh. (Intellectual and political history, 2015)
Table of contents: Introduction. Tocqueville in his Time[-]Chapter 1. Jansenism and Republicanism in France, 1648-1789[-]Chapter 2. Tocqueville, Jansenism, and French Political Culture, 1789-1859[-]Chapter 3. The Necessity of the Political in a Democratic Age (I): The Politics[-]of Providence in the Author's Introduction to Democracy in America[-]Chapter 4. The Necessity of the Political in a Democratic Age (II): Tocqueville's Modern Republicanism and the Dogma of the Sovereignty of the People[-]Chapter 5. The Necessity of the Political in a Democratic Age (III): The Enlightened Interest of the Americans[-]Chapter 6. The Necessity of the Political in a Democratic Age (IV): [-]The Freedom of Education and the "Twin Tolerations" in France, 1843-1850[-]Chapter 7. The Necessity of the Political in a Democratic Age (V): [-]Tocqueville Antinomies, the Political Utility of Religion, and the American Double Foundation[-]Conclusion: Building a Republic for the Moderns[-]Bibliography